National Disaster Management Organisation’s Risk Communication in Ghana: A Case Study of Flood Areas in Accra - Adu, Charles Hanson; Agyepong, Lawrencia (International Journal of Research in Education Humanities and Commerce, 2022)
Risk communication is an integral part of any Risk Management process. This study reports on its importance, the medium, the approach used as well as the factors that influence risk communication in Accra, Ghana. Data obtained from residents through the administration of questionnaires in the flood-prone areas, as well as interviews with the National Disaster Management Organisation (NADMO), the institution mandated to manage the risk of flooding and other emergencies, brought out various issues on the risk communication process in Accra. This study finds that despite the perceived importance of risk communication in the risk management process, risk communication in Accra is hampered by ineffective regulations and a lack of trust by affected residents among other impediments. This research recommends that NADMO must increasingly use the radio as the main medium for conveying risk messages and that the organization must change its “top-down” risk communication approach into a more interactive one.
Research Article
Keywords: National Disaster Management Organisation, Risk Communication, Ghana, Flood Areas, Accra